Arliss Cutter: Breakneck - Book 5 - Cameron, Marc (Thorndike, Maine : Center Point Large Print, 2023)
"Off the northeast coast of Russia, the captain and crew of a small crabbing vessel are brutally murdered by a member of Bratva, the Russian mafia. In Washington, DC, Supreme Court Justice Charlotte Morehouse prepares for a trip to Alaska, unaware that a killer is waiting to take his revenge -- by livestreaming her death to the world. In Anchorage, Alaska, Deputy US Marshals Arliss Cutter and Lola Teariki are assigned to security detail at a judicial conference in Fairbanks. Lola is tasked with guarding Justice Morehouses teenaged daughter while Cutter provides counter-surveillance. Its a simple, routine assignment -- until the mother and daughter decide to explore the Alaskan wilderness on the famous Glacier Discovery train. Hiding onboard are the Russian mobsters, who launch a surprise attack. With no supplies and no connection to the outside world, Cutter and the judge must cross treacherous terrain to stay alive. Two of the mobsters are close behind. The others are on the train with the judges daughter -- and they plan to execute her on camera. With so many lives at stake, Cutter knows there are only two options left: catch the train and kill them all . . . or all will be killed."--
Keywords: United States. -- Supreme Court -- Officials and employees; United States marshals -- Fiction; Railroad trains -- Alaska; Fiction; Wilderness survival -- Fiction; Terrorists -- Fiction; Alaska -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Large print books